Globalization crises, trade, and development in Vietnam - Philip Abbott; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Vietnam has been among the most successful East Asian economies, especially in weathering the external shocks of recent globalization crises - the 1997-98 Asian financial crisis and the 2008-09 great recession, financial crisis and collapse of global trade. Its success contradicts its characterization as an example of export-led growth and highlights the role of the state, particularly in maintaining and influencing investment. Examination of economic performance and policy responses shows rising dependence on foreign finance around each crisis, and actions by the government to counteract that dependence and bolster the domestic economy while continuing to restructure the economy toward greater emphasis on the private sector. Growth, employment and poverty alleviation have been maintained at the expense of renewed inflation, larger budget deficits, and currency depreciation. The stop-go nature of present macroeconomic policy is the consequence of balancing growth versus inflation, responding to severe external shocks and holding to a growth objective in the face of substantial internal and external criticism.
Keywords: F13; F14; O24; O53; 330; trade and development; trade liberalization; foreign direct investment; globalization; WTO accession; asian financial crisis; great recession; Vietnam; Entwicklung; Außenwirtschaft; Globalisierung; Außenhandelsliberalisierung; Direktinvestition; Finanzmarktkrise; Vietnam